Improvement of coagulation efficiency using instantaneous flash mixer (IFM) for water treatment - Byun, S; Oh, J; Lee, BY; Lee, S (ELSEVIER SCIENCE BV, 2005)
A coagulation step is not only economical but is also a very effective process for treating drinking water. Many studies have been devoted to efficient coagulation. As one of those endeavors, the mixing effect of a coagulant has been studied extensively. In this study, a new type of mixing technique, which is called an instantaneous flash mixer, was compared with a mechanical back mixer in order to determine the influence of mixing on the removal of particulates and organic matter. It is characterized by achieving an instantaneous dispersion of coagulants in water coagulation process. The flow characteristics were simulated using CFD (computer fluid dynamics) in order to derive the operational conditions such as the optimum ratio of the nozzle velocity to the main water volume. Subsequently, the removal of the turbidity, dissolved organic carbon and the specific UV absorbance were investigated as the basic parameters for an examination of the coagulation efficiency. The results showed that the instantaneous flash mixing was fairly efficient in diminishing the coagulant dose, even < 5 mg/L of poly-aluminum chloride and by improving the removal of the turbidity and dissolved organic carbon. This was attributed to the fact that, among the coagulation mechanisms, charge neutralization made a larger contribution to the performance, which must be achieved by the instantaneous mixing of a coagulant within 1 s using a jet dispersion near the nozzle. Further studies aimed at revealing the coagulation performance in terms of the organic components by the NOM separation are being investigated for a full scale application. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ENHANCED COAGULATION; HUMIC SUBSTANCES; ORGANIC-MATTER; FLOCCULATION; DESIGN; ALUM; OPTIMIZATION; REACTIVITY; BEHAVIOR; RESIN